What should a dentist be aware of concerning symptoms of sleep disorders in the oral cavity? - Smardz, Joanna; Florjanski, Wojciech; Orzeszek, Sylwia; Malysa, Andrzej; Zietek, Marek; Wieckiewicz, Mieszko (Journal of Stomatology, 2019)
Sleep bruxism (SB) is a common and complex phenomenon that can result in serious clinical consequences concerning the stomatognathic system including damage to dental hard tissues, especially tooth wear, damage to prosthetic restorations, damage to the periodontium and oral mucosa, and a spectrum of symptoms affecting masticatory muscles. However, there are other conditions with similar clinical manifestations that may resemble or even in some cases mimic SB. The aim of this study was to evaluate the most common sleep-related conditions that can cause clinical implications similar to SB and to emphasize the methods of carrying out a proper differential diagnosis. PubMed, Web of Science, and Scopus databases were searched for current literature on the manifestation of selected sleep disorders in the stomatognathic system. Forty-one articles were finally included in this review. Conditions such as oromandibular myoclonus, dystonia, Parkinson’s disease and parkinsonism, epileptic and non-epileptic motor phenomena were included in this review as potentially mimicking the symptoms of sleep bruxism. Included studies indicate that the combination of accurate medical history interview, thorough clinical examination and video-polysomnography seems to be the key to proper differential diagnostics between SB and other medical conditions that can occur during sleep and present similar clinical symptoms affecting the stomatognathic system.